Comparative Analysis of the Therapeutic Effects of MSCs From Umbilical Cord, Bone Marrow, and Adipose Tissue and Investigating the Impact of Oxidized RNA on Radiation-Induced Lung Injury - Rui Zhai; Fumin Tai; Kexin Ding; Xin Tan; Hujie Li; Zhengyue Cao; Changhui Ge; Xiaofei Zheng; Hanjiang Fu (Stem Cells International)
Radiation-induced lung injury (RILI) is frequently observed in patients undergoing radiotherapy for thoracic malignancies, constituting a significant complication that hampers the effectiveness and utilization of tumor treatments. Ionizing radiation exerts both direct and indirect detrimental effects on cellular macromolecules, including DNA, RNA and proteins, but the impact of oxidized RNA in RILI remains inadequately explored. Mesenchymal stem cells (MSCs) can repair injured tissues, and the reparative potential and molecular mechanism of MSCs in treating RILI remains incompletely understood. This study aimed to investigate the therapeutic effects and mechanisms of action of three distinct sources of MSCs, including human umbilical cord mesenchymal stem cells (UCMSCs), bone marrow mesenchymal stem cells (BMSCs), and adipose-derived stem cells (ADSCs), in thoracically irradiated mice. Comparative analysis revealed that all three types of MSCs exhibited the ability to mitigate radiation-induced inflammatory infiltration, alveolar hemorrhage, and alveolar wall thickening in the lung tissue of the mice. MSCs also attenuated RILI by decreasing inflammatory factors, upregulating anti-inflammatory factor expression, and reducing collagen accumulation. Immunohistochemical results showed that all three MSCs reduced radiation-induced cell apoptosis and promoted the regeneration of lung tissue cells. The analysis of malondialdehyde (MDA) and 8-hydroyguanosine (8-OHG) content indicated that MSCs possess reparative properties against radiation-induced oxidative damage in lung tissue. The study provides evidence that UCMSCs are a more appropriate therapeutic option for RILI compared to BMSCs and ADSCs. Additionally, MSCs effectively reduce the accumulation of oxidized RNA in RILI, thereby, presenting a unique avenue for investigating the underlying mechanism of MSC-based treatment for RILI.